Palmitic acid impairs INS-1 cells and alters the global gene expression profile: PA affected global gene expression profile - Feng, Xiaotao; Ren, Wei; Tang, Yuxiang; Wen, Ruyan; Duan, Huiming; Yan, Li (Cellular and Molecular Biology, 2022)
Chronic elevated free fatty acids (FFAs) impair pancreatic β cells, but the mechanisms remain elusive. In this study, palmitic acid (PA) impaired viability and glucose-stimulated insulin secretion of INS-1 cells. Microarray analysis showed that PA markedly altered the expression of 277 probe sets of genes with 232 upregulated and 45 downregulated (fold change ≥ 2.0 or ≤ -2.0; P < 0.05). Gene Ontology analysis displayed a series of the biological process of the differentially expressed genes, such as intrinsic apoptotic signaling pathway in response to endoplasmic reticulum (ER) stress and oxidative stress, inflammatory response, positive regulation of macroautophagy, regulation of insulin secretion, cell proliferation and cycle, fatty acid metabolic process, glucose metabolic process and so on. Kyoto Encyclopedia of Genes and Genomes analysis demonstrated molecular pathways with which the differentially expressed genes associated, including NOD-like receptor, NF-κB and PI3K-Akt signaling pathways, apoptosis, adipocytokine signaling pathway, ferroptosis, protein processing in ER, fatty acid biosynthesis and cell cycle. Moreover, PA promoted protein expression of CHOP, cleaved caspase-3, microtubule-associated proteins light chain 3 (LC3)-II, NOD-like receptor pyrin domain containing 3 (NLRP3), cleaved IL-1β and Lcn2, increased reactive oxygen species, apoptosis and the ratio of LC3-II/I, and reduced p62 protein expression, intracellular glutathione peroxidase and catalase levels, suggesting activation of ER stress, oxidative stress, autophagy and NLRP3 inflammasome. The results indicate the impaired role of PA and the global gene expression profile of INS-1 cells following PA intervention, providing new insights into the mechanisms involving the damage of pancreatic β cells by FFAs.